Audit Quality of Outsourced Information Technology Controls. Issue 9 (28th August 2014) - Mazza, Tatiana; Azzali, Stefano; Fornaciari, Luca
Abstract : Purpose: To test the positive relationship between Audit Quality (AQ) of Outsourced Information Technology Controls (ITC) and Information Technology Audit Quality (ITAQ). Design/methodology/approach: Factor analysis, OLS regressions and simulations. Findings: Scoping and Planning phases of the audit cycle account for about 69% of ITAQ. The AQ of outsourced ITC is strongly and directly related to ITAQ. Improvement of AQ of outsourced ITC may be achieved through evaluation of control design and operating effectiveness by Service Auditor as well as direct evaluation by the client in Service Provider location. Research limitations/implications: Sample size and input items in factor analysis. Practical implications: Companies and auditors could improve ITAQ through a better organization of the Scoping and Planning activities; they could also improve the AQ of outsourced ITC using direct evaluation in the Service Provider location supplemented with Service Auditor reports. Regulators could refine or change laws and frameworks to take into account the factors of ITAQ and the methodology of evaluation of outsourced ITC. Originality/value: Private data collected by questionnaire. The measures of ITAQ and the OLS model could be tested in future research, in countries with different frameworks and regulations related to audit quality, different weight of outsourced IT and other characteristics related to clients, Service Providers and Service Auditors.